Prevention of Primary Postpartum Hemorrhage with Treatment of Parenteral Iron in Mild to Moderate Anemic Patients - Nadir, Benish; Jabeen, Musarat (Indus Journal of Bioscience Research, 2025)
Background: Iron deficiency anemia is common in pregnancy and is of great concern with regards to maternal health as well as increasing the risk of complication such as primary postpartum hemorrhage. Parenteral iron administration is one option that has become available for anemia but its role in preventing postpartum hemorrhage in pregnant women with mild to moderate anemia is an area that is in need of further investigation. Objective: To determine the efficacy of parenteral iron in prevention of primary postpartum hemorrhage in mild to moderate anemic patients. Study Design: Quasi-experimental study. Duration and Place of Study: The study was conducted between August 2024 and February 2025 at the Department of Obstetrics and Gynaecology, Saidu Group of Teaching Hospitals, Swat. Methodology: A total of 139 women with singleton pregnancy in the 18–40 years range with anemia with an Hb of 8-12 g/dL were included in the recruitment. The subjects received intravenous iron sucrose 600 mg that was given in three consecutive days starting from 28 weeks’ gestational age. The absence of immediate postpartum hemorrhage in the form of blood loss of ≥1000 ml with cesarean section or ≥500 ml with vaginal delivery was the primary outcome. Results: The subjects’ mean age was 29.30 ± 4.42 years while the level of hemoglobin was 9.13 ± 1.02 g/dL upon enrollment. The parenteral iron therapy had an efficacy of 92.8% with no correlations of significance between demographic variables like age, BMI, or mode of delivery with efficacy. Of interest was that there was an inverse correlation of significance between hemoglobin level and efficacy such that those with the lowest baseline hemoglobin levels had the best response to the therapy. Conclusion: Parenteral iron sucrose is an effective and well-tolerated treatment for preventing primary postpartum hemorrhage in anemic pregnant women, with high efficacy across various demographic groups.